Materialismo y arte en Walter Benjamin - Sarasola, Beñat (2022)
Materialism and Art in Walter Benjamin”. This paper analyses the issue of materialism and its relationship with art in Walter Benjamin’s thought. This is a controversial issue in the debates around Benjamin. The article examines in detail Benjamin’s two fundamental texts on this topic: The Author as Producer and The Work of Art in the Era of Mechanical Reproduction. Before this, the paper puts the problem into context, considering the times and, in particular, Benjamin’s relationship with Brecht, which was seen as one of the key elements to understand Benjamin’s material turn. This fact disturbed some of his colleagues —like Adorno, Horkheimer and Karplus— who saw Brecht as an excessively orthodox materialist. This paper argues, however, that, although Benjamin turned towards materialist positions throughout the decade of the 30s, his materialism was not like the one defended by the Marxist orthodoxy of the time, though, indeed, it went beyond Adorno’s modernist approaches.